In Candida albicans, white-opaque switchers are homozygous for mating type. - Lockhart, Shawn R (2002)
The relationship between the configuration of the mating type locus (MTL) and white-opaque switching in Candida albicans has been examined. Seven genetically unrelated clinical isolates selected for their capacity to undergo the white-opaque transition all proved to be homozygous at the MTL locus, either MTLa or MTLalpha. In an analysis of the allelism of 220 clinical isolates representing the five major clades of C. albicans, 3.2% were homozygous and 96.8% were heterozygous at the MTL locus. Of the seven identified MTL homozygotes, five underwent the white-opaque transition. Of 20 randomly selected MTL heterozygotes, 18 did not undergo the white-opaque transition. The two that did were found to become MTL homozygous at very high frequency before undergoing white-opaque switching. Our results demonstrate that only MTL homozygotes undergo the white-opaque transition, that MTL heterozygotes that become homozygous at high frequency exist, and that the generation of MTL homozygotes and the white-opaque transition occur in isolates in different genetic clades of C. albicans. Our results demonstrate that mating-competent strains of C. albicans exist naturally in patient populations and suggest that mating may play a role in the genesis of diversity in this pernicious fungal pathogen.